2016
DOI: 10.1007/s13668-016-0161-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dietary Omega-3s on Muscle Composition and Quality in Older Adults

Abstract: This review will focus on findings from the few studies performed to date in humans to examine changes in muscle protein turnover, lean or muscle mass and physical function following fish oil-derived omega-3 fatty acid treatment. Although considerable gaps in our current knowledge exist, hypertrophic responses (e.g., improvements in the rate of muscle protein synthesis and mTOR signaling during increased amino acid availability and an increase in muscle volume) have been reported in older adults following prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 83 publications
(126 reference statements)
1
13
0
Order By: Relevance
“…The same logic applies to MIS vs. single-nutrient supplementation as the former theoretically stimulates several processes simultaneously, thus 'circumventing' the main limitation of using nutritional monotherapies, such as whey or BCAAs, e.g., anabolic resistance with aging. Common nutrients with documented SM benefits in MIS include whey [53,69,70], vitamin D [53,61,62,69,70], polyunsaturated fatty acids (n-3 PUFAs; EPA and DHA [53,63,64,69,70]), and creatine [53,[65][66][67][68][69][70]. As previously demonstrated by Bell et al, this blend of nutrients may be safely combined to potentiate SM growth independently or in conjunction with supervised RE/HIIT [53].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The same logic applies to MIS vs. single-nutrient supplementation as the former theoretically stimulates several processes simultaneously, thus 'circumventing' the main limitation of using nutritional monotherapies, such as whey or BCAAs, e.g., anabolic resistance with aging. Common nutrients with documented SM benefits in MIS include whey [53,69,70], vitamin D [53,61,62,69,70], polyunsaturated fatty acids (n-3 PUFAs; EPA and DHA [53,63,64,69,70]), and creatine [53,[65][66][67][68][69][70]. As previously demonstrated by Bell et al, this blend of nutrients may be safely combined to potentiate SM growth independently or in conjunction with supervised RE/HIIT [53].…”
Section: Discussionmentioning
confidence: 90%
“…Beyond protein supplementation, vitamin D [ 61 , 62 ], polyunsaturated fatty acids (n-3 PUFAs; EPA and DHA [ 63 , 64 ]), and creatine [ 65 , 66 , 67 , 68 ] have documented SM benefits and may be safely combined with exercise therapy in older adults. The efficacy of protein-based MIS in older adults was recently demonstrated by Bell et al, who found that whey protein, creatine, EPA/DHA, and vitamin D enhanced lean mass, strength, cognition, n-3 index, and lowered markers of inflammation in older males [ 53 , 69 , 70 ].…”
Section: Introductionmentioning
confidence: 99%
“…A possible link can be found with an increased insulin sensitivity, as it was shown that PUFA supplementation leads to increased phosphorylation of the insulin receptor and its downstream signaling (Kamolrat and Gray, 2013 ; Wei et al, 2013 ). Furthermore, enhanced insulin signaling induces vasodilation, which increases amino acid availability (Smith, 2016 ).…”
Section: Inflammation-reducing Approaches Targeting Age-related Sarcomentioning
confidence: 99%
“…Previous systematic reviews evaluating the effects of omega-3, omega-6 or total PUFA on skeletal muscle and bone health, sarcopenia or fracture risk have been limited to specific PUFAs (usually omega-3) [19][20][21][22], specific population subgroups (e.g. post-menopausal women) [19] or specific outcomes (e.g.…”
Section: Introductionmentioning
confidence: 99%